Hematological evidence of selective dysmegakaryocytopoiesis in a dog with canine ehrlichiosis - Vásquez Y., Alvaro (2020)
The case of a two-year-old English sheep bitch that was taken to the Small Animal Clinic of the Faculty of Veterinary Medicine, Universidad Nacional Mayor de San Marcos for presenting recent lethargy is described. Blood tests revealed pancytopenia, presence of morulae compatible with Ehrlichia spp in leukocytes, dysproteinaemia and seropositivity against E. canis / E. ewingii. The presence of multiple dysplastic megakaryocytes, which exhibited alterations such as asynchrony of nuclear maturation, nuclei not lobed to hypolobulated, pseudo-articulated aspect of the nucleus and megakaryocytic emperipolesis of neutrophils were observed, without myelodysplastic alterations in the remaining cell lineages. The characteristics described represent the first haematological evidence of selective dysmegacariocytopoiesis in a dog with canine ehrlichiosis in Peru.